As Interfaces entre Bullying Escolar e Altas Habilidades/Superdotação: uma revisão sistemática de literatura - Poisk, Camilla Casotti (2023)
School bullying is a type of peer violence that manifests itself on school grounds and is characterized by the recurrence of hostile actions aimed at violating the victim's biopsychosocial integrity. Given that the inability to deal with differences is one of its main roots, this phenomenon is the subject of countless Brazilian investigations aimed at the target audience of Special and Inclusive Education. With regard to these students, on the one hand, there has been a consolidated interest in those with disabilities or global development disorders, but on the other hand, there is a lack of Brazilian research into bullying among the gifted population. Given the need to search for international production and to disseminate this debate in Brazil, this study was a systematic literature review without meta-analysis, with a quantitative-qualitative approach, guided by the question: "How is school bullying experienced by gifted adolescents?", with the general objective of analyzing how school bullying is experienced by gifted adolescents. The specific objectives were to present the state of knowledge on the object of study in the last five years; to identify the predictors, expressions and impacts of school bullying experienced by gifted adolescents and to assess whether this population can be considered a risk group for school bullying. To achieve this, the StArt - UFSCAR software was used to conduct this RSL, which included 15 scientific articles retrieved from the following indexed electronic databases: BVS, ERIC, Portal de Periódicos CAPES, Redalyc, Scielo, Scopus and Springer Link. The analysis of the data extracted from the literature was based on the phenomenological perspective. The results were grouped into six categories: portrait of the phenomenon, predictors, consequences and coping strategies, parents and teachers, protective factors and prevention strategies, limitations. In short, it was found that gifted adolescents with are involved in school bullying, occupying the positions of victim, victim-aggressor, aggressor and bystander, with higher rates of victimization compared to adolescents without this condition. Some particularities of giftedness were recognized as predictors of aggression, which often takes on verbal expression and has negative consequences for biopsychosocial development. It was concluded that this population can be considered more vulnerable to bullying in schools. It is hoped that this research will benefit the expansion and visibility of recent scientific production on this phenomenon, since this knowle